Enabling participatory monitoring and evaluation: Insights for conservation practitioners and organizations - Amanda Sigouin; Ana Luz Porzecanski; Erin Betley; Nadav Gazit; Peter Lichtenthal; Samantha H. Cheng; Pablo Pacheco; Shauna L. Mahajan (Conservation Science and Practice)
Abstract Mounting environmental crises and the persistent factors driving them require a reconsideration of conservation approaches. Participatory monitoring and evaluation (PME) is increasingly valued as a way for Indigenous peoples and local community actors to lead or engage in conservation activities that directly affect them. While research shows that PME can yield favorable outcomes for communities (e.g., knowledge co‐production, social learning, and trust building) and for conservation, practical insights are scattered. Here we draw from the literature and discussions with professionals in the field to distill practical guidance for the design, implementation, and support of PME in conservation. This perspective highlights three themes for effective PME: navigating collaborations, working within local and diverse cultural contexts, and co‐managing PME resources (including resources needed for PME and generated by PME). We recommend that practitioners and organizations, including our own, engage with these focal areas by reflecting on the purpose of PME, learning from relevant experiences, strengthening capacity for PME collaborations, and supporting PME through innovative and flexible financing. We see these actions as leverage points to promote effective PME and advance inclusive approaches to biodiversity conservation.